Talent migration in NCAA division I tennis: An exploratory study - Parrish, C.; Otto, K. A.; Dodson, C. (Western Carolina University, 2020)
The recruitment of international-student athletes (ISAs) to NCAA schools in the United States has been a feature of intercollegiate athletics since the late 1940`s and an influx of foreign-born athletes became evident from the late 1960s and through the 1970s (Stidwell 1984). More recently, the number of ISAs increased drastically from the 1990s to the 2000s and this growth trend has continued. Similar to Chepyator-Thomson et al.`s (2016) research on migration patterns of ISAs in NCAA basketball and Kirk and Weaver`s (2019) work on ISAs in NCAA soccer, the purpose of this study was to explore talent migration in NCAA Division I (DI) tennis. The authors incorporate discussions on globalization and world-system theory to explicate global sport labor migration and analyze descriptive player and coach data to understand: 1) the extent of ISAs competing in NCAA DI tennis in comparison to other sports; 2) distribution of tennis ISAs across three DI categories and thirty-one conferences; 3) migration patterns of DI tennis ISAs with respect to country and city of origin; and, 4) the percentage of international tennis coaches in DI. Findings indicate tennis has the highest percentage of ISAs among all NCAA sports, ISAs make up the majority of all men`s and women`s tennis players at the DI level, Spain is the top donor nation, and the percentage of international coaches for DI teams is approximately 30%. The authors conclude the paper with commentary informed by veteran DI tennis coaches regarding the impact of the COVID-19 pandemic on the future of college tennis.